Ketene as a Reaction Intermediate in the Carbonylation of Dimethyl Ether to Methyl Acetate over Mordenite1. Issue 25 (12th May 2015) - Rasmussen, Dominik B.; Christensen, Jakob M.; Temel, Burcin; Studt, Felix; Moses, Poul Georg; Rossmeisl, Jan; Riisager, Anders; Jensen, Anker D.
Abstract Unprecedented insight into the carbonylation of dimethyl ether over Mordenite is provided through the identification of ketene (CH2CO) as a reaction intermediate. The formation of ketene is predicted by detailed DFT calculations and verified experimentally by the observation of doubly deuterated acetic acid (CH2DCOOD), when D2O is introduced in the feed during the carbonylation reaction.